2016
DOI: 10.1021/acssuschemeng.6b01481
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Bulk Metallurgical Silicon into Photocatalytic Nanoparticles by Copper-Assisted Chemical Etching

Abstract: Low-grade metallurgical silicon (MG-Si, purity ∼98%−99%, $1/kg) with annual production over six million tons is an attractive feedstock to produce active photocatalysts. However, MG-Si is known as an electronically dead material due to serious charge recombination associated with high metal impurity levels. Upgrading MG-Si close to solar grade is essential to achieve desired performance; nevertheless, the traditional silicon refinement process is cost ineffective, has high energy consumption, and causes enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…This acid reacts with GO functional groups due to carboxyl and hydroxyl functional groups and therefore causes Si nanoparticles to adhere to graphene plates [50]. Also, the presence of this acid and the CTAB prevented the nanoparticles from bonding to each other and caused the nanoparticles to spread on all rGO surfaces.As previously mentioned, in the synthesis 3, ultrasonic was used for the initial combination of Si and GO powder.…”
Section: -2: Morphology Of Si Nps-rgo Compositionmentioning
confidence: 99%
“…This acid reacts with GO functional groups due to carboxyl and hydroxyl functional groups and therefore causes Si nanoparticles to adhere to graphene plates [50]. Also, the presence of this acid and the CTAB prevented the nanoparticles from bonding to each other and caused the nanoparticles to spread on all rGO surfaces.As previously mentioned, in the synthesis 3, ultrasonic was used for the initial combination of Si and GO powder.…”
Section: -2: Morphology Of Si Nps-rgo Compositionmentioning
confidence: 99%
“…There are two types, including acid etching and metal-assisted chemical etching (MACE). [6][7][8][9] For the acid etching, the metal removal efficiency increases proportionally with the surface area of MG-Si particles. Zong and co-workers obtained nano-Si of 99.999% (5N) purity from low-grade ferro silicon (84%) using an acidic etchant consisting of HF, HNO 3 , and HCl.…”
Section: Si Purification Routes For the Photovoltaic And Solar Water-splitting Applicationsmentioning
confidence: 99%
“…By contrast, MACE can process coarse MG-Si particles since it is a self-catalyzing porosification process. [7][8][9] The MG-Si particle size can be tens of micrometers without compromising purification effect as the metal nanoparticles can drill deep into the silicon particles and expose new surfaces. Our group achieved MG-Si purification from 99.74% to 99.9884% via Ag-based MACE.…”
Section: Si Purification Routes For the Photovoltaic And Solar Water-splitting Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…By exposing the solidified silicon to the acid solution, impurities located at grain boundaries of precipitates between the primary silicon grains can be carried away, and pure Si can be obtained. Considerable research has been performed to study the impurity extraction from MG-Si by acid leaching. It has been found that most of the metallic impurities can be effectively extracted by adjusting a variety of processing parameters like leaching temperature, time, acid combination, and particle size, but the effective P extraction by direct leaching of MG-Si still remains a challenge. Even though it has been theoretically and experimentally confirmed that P tends to segregate along Si grain boundaries, its segregation coefficient ( k p = 0.35) is still relatively high compared to metallic impurities, which is usually less than 10 –3 .…”
Section: Introductionmentioning
confidence: 99%